1979
DOI: 10.2118/7061-pa
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Phase Equilibria on the CO2 Displacement Mechanism

Abstract: Carbon dioxide flooding under miscible conditions is being developed as a major process for enhanced oil recovery. This paper presents results of research studies to increase our understanding of the multiple-contact miscible displacement mechanism for CO2 flooding. Carbon dioxide displacements of three synthetic oils of increasing complexity (increasing number of hydrocarbon components) are described. The paper concentrates on results of laboratory flow studies, but uses results of phase-equilibria and numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(60 citation statements)
references
References 0 publications
3
56
1
Order By: Relevance
“…mole% of methane, 30 mole% of n-butane and 45 mole% of n-decane. This standard gasoil system has been reported to have a slim-tube minimum miscibility pressure (MMP) of 1700 psia at 160 o F (Metcalfe and Yarborough, 1979). This miscibility pressure is further reproduced with phase diagram measurements (Metcalfe and Yarborough, 1979) and analytical model predictions (Monroe et al, 1990;Orr et al, 1993).…”
Section: Principles and Equations Usedmentioning
confidence: 61%
See 2 more Smart Citations
“…mole% of methane, 30 mole% of n-butane and 45 mole% of n-decane. This standard gasoil system has been reported to have a slim-tube minimum miscibility pressure (MMP) of 1700 psia at 160 o F (Metcalfe and Yarborough, 1979). This miscibility pressure is further reproduced with phase diagram measurements (Metcalfe and Yarborough, 1979) and analytical model predictions (Monroe et al, 1990;Orr et al, 1993).…”
Section: Principles and Equations Usedmentioning
confidence: 61%
“…Metcalfe and Yarborough (1979) have studied the phase behavior by performing various experiments on reservoir fluids using CO 2 as the displacing phase and have concluded that more than one mechanism (vaporizing and condensing) is possible for a CO 2 -reservoir fluid system and that reservoir temperature and displacement pressure determine the type of mechanism (vaporization, condensing or vaporizing/condensing) that will control the displacement process.…”
Section: Discussion On Co2 Drive Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…cell (7,7,2) cell (9,9,2) b) Viscosity of the gas in the second layer As Fig. 3.39 indicates, the breakthrough gas into each cell has the highest viscosity, since it is rich in intermediate components of the oil.…”
Section: Fig 338-typical Relative Permeability Curvementioning
confidence: 99%
“…The first exemplification is given here for the MY10 mixture, taken from Metcalfe and Yarborough (1979). The MY10 synthetic mixture contains 10 normal-alkanes, with composition and BIPs of methane (taken from Firoozabadi and Pan, 2002) with the remaining components given in Table 1.…”
Section: The My10 Mixturementioning
confidence: 99%